Comparative Analysis of Computer Vision Syndrome (CVS) Risk Factors in Digital-Based Elementary School Students - Alma, Siti; Zahara, Meutia; Hermansyah, Hermansyah (Indonesian Journal of Global Health Research, 2025)
The use of digital electronic devices is increasingly widespread among students, both in academic and non-academic contexts, but this can have negative impacts such as Computer Vision Syndrome (CVS). This study aims to analyze the comparative risk factors for CVS in digital-based elementary school students in Banda Aceh City and conventional-based students in Aceh Besar Regency. The study used a cross-sectional design with a total of 64 respondents using Simple Random Sampling technique, consisting of 32 students from each school. Data were collected between 15–30 August. The analysis was carried out using the Mann-Whitney U test, Independent Sample t-test, and logistic regression. The results showed a higher prevalence of CVS in digital-based students (75%) than in conventional. The average time of using electronic devices in the digital group was 8 hours/day, higher than the conventional group (5 hours/day). There was a significant difference in the duration of electronic device use between the two groups (p=0.0001). The most dominant factor associated with CVS was the duration of digital electronic device use in a day (OR=2.05; 95% CI=1.41–2.99; p=0.0001). This study emphasizes the importance of regulating the time of digital device use in children.